Zygotic genome activation in isogenic and hybrid plant embryos. (February 2016) - Del Toro-De León, Gerardo; Lepe-Soltero, Daniel; Gillmor, C Stewart
Highlights: Isogenic embryos show delayed activation for many, but not all, paternal alleles. Embryos hybrid for certain combinations of ecotypes show equal parental contributions to early embryogenesis. Altered paternal gene activation in hybrids may have an epigenetic basis. Abstract : Zygotic genome activation (ZGA) is the onset of large-scale transcription that occurs after fertilization. In animal embryos, ZGA occurs after a period of transcriptional quiescence that varies between species. In plants, the timing of ZGA may also vary between species, and may or may not occur in a parent-of-origin dependent manner: some studies have shown a maternal bias in mRNA transcripts and gene activity in early embryogenesis, while other experiments have found the contribution of maternal and paternal genomes to be equal. In order to differentiate between maternal and paternal mRNAs, RNA sequencing studies of ZGA in plants have used embryos hybrid for polymorphic accessions. A recent genetic assay in Arabidopsis demonstrated significant variation in paternal allele activity between some hybrid combinations and isogenic embryos, as well as between different hybrid combinations, suggesting a possible source for conflicting results obtained by various experiments on paternal genome activation. We review recent literature on paternal genome activation studies in the zygote in both isogenic and hybrid embryos, and discuss possible explanations for the effects of hybridization on gene expression in early embryogenesis in plants.